Megalithism in Catalonia: A brief overview - Josep Tarrús i Galter (Institut d'Estudis Catalans, 2021)
The study of megalithism in Catalonia, especially southern Catalonia (south of the Pyrenees), has changed considerably in the past four decades (1980-2020) thanks to several extraordinarily important excavations. They include the dolmen in Els Reguers de Seró (Artesa de Segre) and the menhir in El Pla de les Pruneres (Mollet del Vallès), both of which yielded heretofore unseen engravings, and most importantly the long-term campaigns focused on specific regions, such as the Alt Empordà, Tavertet (Osona) and, more recently, Maresme-Baix Vallès. Also worth noting is the work done on the western dolmen region, such as in Odèn (Solsonès), and the new excavations and studies on underground Neolithic cists from the Solsonian (Solsonès), which have now been included in megalithism in Catalonia, a much more complex, long and varied period than we imagined back in the 1970s. Indeed, the timeline of Catalan megalithism currently stretches from the early middle Neolithic (4500 BC) to the onset of the Bronze Age (1800 BC), that is, more than 2500 years through Neolithic, Chalcolithic and Bronze-Age cultural groups which shared the custom of burying their dead in more or less monumental stone graves, their hallmark. Alongside the graves, these recent decades have also finally revealed some of the settlements where their builders lived, such as the one in Ca n’Isach (Palau-saverdera, Alt Empordà); new menhirs and sites or cromlechs consisting in menhirs or built around menhirs near the habitat areas have been discovered; and new megalithic statuary, such as the one from Ca l’Estrada (Canovelles, Granollers). These are similar to the megalithic world in southeast France, while also enriching the known megalithic art records here in Catalonia, which until now were primarily centred around schematic anthropomorphic and geometric engravings in some megalithic graves in the Alt Empordà/Roussillon/Conflent.